EVALUATION OF LAND SUITABILITY FOR AVOCADO CULTIVATION IN THE BAWANG GAJAH SUB-WATERSHED, CENTRAL ACEH REGENCY: EVALUASI KESESUAIAN LAHAN TANAMAN ALPUKATDI SUB DAS BAWANG GAJAH KABUPATEN ACEH TENGAH - Yasinta Fadilla; Halim Akbar; Yusra (PT. ROCE WISDOM ACEH, 2026)
Avocado (Persea americana) is an important horticultural crop with high nutritional value and economic potential. Land suitability evaluation is essential to determine land capability for optimal crop growth and sustainable production. This study aimed to assess the land suitability class for avocado cultivation in the Bawang Gajah Sub-Watershed, Central Aceh Regency. The study employed a survey-based approach comprising preparation, a preliminary survey, a field survey, and data analysis. Soil sampling was conducted based on the Land Mapping Unit (LMU) derived from the overlay of slope, land use, and soil type maps using GIS techniques. The results indicated that land suitability for avocado cultivation in the study area was classified as marginally suitable (S3). LMU 2 was limited by soil texture, while soil texture, P₂O₅, K₂O, and slope constrained LMU 3. LMU 4, 6, and 7 were limited by soil texture, P₂O₅, and slope, whereas P₂O₅ and slope constrained LMU 14. These limitations suggest that soil physical properties, nutrient availability, and topographic conditions are the main constraints for avocado cultivation. Improvement measures such as applying organic matter, constructing terraces, and applying balanced phosphorus and potassium fertilizers are recommended to enhance land suitability.